Benton-Cohen, Katherine: "Inventing the Immigration Problem: The Dillingham Commission and Its Legacy". Cambridge, Harvard University Press, 2018. 352 pp - Saitua, Iker (Cuadernos de Historia Contemporánea, 2019)
Benton-Cohen, Katherine: "Inventing the Immigration Problem: The Dillingham Commission and Its Legacy". Cambridge, Harvard University Press, 2018. 352 pp